Epilepsy in the Sanaga‐Mbam valley, an onchocerciasis‐endemic region in Cameroon: electroclinical and neuropsychological findings. Issue 3 (3rd August 2021) - Morin, Alexandre; Guillaume, Maxime; Ngarka, Leonard; Tatah, Godwin Y.; Siewe Fodjo, Joseph Nelson; Wyart, Guillaume; Nokam, Ghislain; Tchoumi, Thierry; Nkinin, Mary Bello; Njamnshi, Wepnyu Y.; Chokote, Eric‐Samuel; Boussinesq, Michel; et al.
Abstract: Objective: Epilepsy is highly prevalent in onchocerciasis‐endemic African regions. Various types of epilepsy have been described in such regions based essentially on clinical characteristics. Methods: We conducted a clinical, neurophysiological and neuropsychological study of epilepsy in the onchocerciasis‐endemic region of Ntui, Sanaga‐Mbam area, Cameroon. Results: One hundred and eighty‐seven persons with presumed epilepsy were recruited in an epilepsy clinic in Ntui. Epilepsy was clinically confirmed in 144 (79%) subjects, 69 (46.0%) of them met the onchocerciasis‐associated epilepsy (OAE) criteria, and 51 of 106 tested (48.1%) presented Ov16 antibodies. Electroencephalograms (EEG) were recorded in 91 participants, of which 36 (33%) were considered abnormal and 27 of 36 (75%) revealed bifrontotemporal spike and slow waves. Concerning the neuropsychological evaluation, 29% showed severe global cognitive impairment, 28% severe episodic memory impairment, and 66% severe frontal cognitive impairment. Half of the persons with epilepsy (PWE) suffered from a mental disorder. Significance: In PWE in the Sanaga‐Mbam area in Cameroon, we observed EEG patterns similar to those described among persons with OAE, including nodding syndrome in other onchocerciasis‐endemic areas. Most PWE presented with severe cognitive impairment. We hypothesize that onchocerciasis may induce neurocognitive disorders and epilepsy via a mechanism that involves mainly the frontal and temporal regions of the brain.